2005
DOI: 10.1021/ie0492348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Extender on Phase Mixing and Coating Properties of Polyurethane Ureas

Abstract: Structural effects of chain extender on phase mixing and coating properties of polyether-based moisture-cured polyurethane ureas (MCPUs) were determined with a polytetramethylene glycol (PTMG-1000), trimethylol propane (TMP), and isophorone diisocyanate (IPDI)-based system. The reaction of PTMG/TMP/IPDI was carried out using a NCO/OH ratio of 1.6:1. The excess isocyanate of the prepolymer was chain extended in the ratio of 2:1 (NCO/OH) with different aliphatic diols and 4:1 with different aromatic diamines jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 46 publications
6
77
0
Order By: Relevance
“…It seems that the MPD chain extender perturbs the formation of hard segment aggregate morphology, whereas the straight chain 1, 4-butanediol provides more phase-separated morphology. Chattopadhyay et al observed the same result in the synthesis of polyurethanes with different chain extenders [30]. In addition, we have deconvoluted the -CQO stretching zone of the PU/Al 2 O 3 samples to understand the effect of Al 2 O 3 nanoparticles on the phase mixing behavior of the samples.…”
Section: Atr-ftir Characterizationsupporting
confidence: 61%
“…It seems that the MPD chain extender perturbs the formation of hard segment aggregate morphology, whereas the straight chain 1, 4-butanediol provides more phase-separated morphology. Chattopadhyay et al observed the same result in the synthesis of polyurethanes with different chain extenders [30]. In addition, we have deconvoluted the -CQO stretching zone of the PU/Al 2 O 3 samples to understand the effect of Al 2 O 3 nanoparticles on the phase mixing behavior of the samples.…”
Section: Atr-ftir Characterizationsupporting
confidence: 61%
“…As the APTS content increases, the C-O/ (C-C/C-H) ratio decreases from 0.919 to 0.510. It is reported that low surface energy soft segment resides towards the top surface and high surface [44][45]. Therefore, it can be concluded that the addition of APTS promotes the phase mixing of polyurethane.…”
Section: Xps Analysismentioning
confidence: 95%
“…XPS has been extensively utilized to study the surface functionalization and phase mixing for polyurethane materials [43][44]. The elemental compositions from the XPS survey spectra (Figure 8) and the peak area ratio from the de-convoluted spectra are presented in Table 3.…”
Section: Xps Analysismentioning
confidence: 99%
“…Cure of MCPU advances with progress of time and produces crosslink networks by the diffusion of moisture, nucleophilic attack and generation of primary amine that further react to produce urea bonds [2,3]. As the chemical reaction proceeds, urea chain length increases and the interaction parameters between the polyether soft and polyurea hard segment also changes.…”
Section: Introductionmentioning
confidence: 99%